Contribution a la connaissance de la nourriture de certains bivalves de la Mer Noire - Gomoiu, Marian Traian; Ușurelu, Mioara (Cercetări Marine - Recherches Marines, 2026)
Analyses of the contents of the digestive tract of 9 bivalves from the Romanian Black Sea shore are presented in the paper. The amounts of the 86 phytoplankton species found by authors are insufficient to meet the food requirements of the animals.